STAKEHOLDER RESPONSE TO INFORMATION ON SOCIAL RESPONSIBILITY AND INCOME SMOOTHING - Nanggala, Ardhya Yudistira Adi (Indonesian Journal of Accounting and Governance, 2023)
Financial statements are a collection of information that the company conveys to stakeholders. Relevant information can change the actions of users of information. This study analyzes the responses of shareholders and the public to social responsibility information and artificial accounting actions of companies. The data used represents manufacturing companies in Indonesia that are listed on the Indonesian Stock Exchange for the 2018-2021 period. The study tested 64 firm panel data using Smart PLS software. Of the five hypothetical suggestions, two suggestions were rejected, and three were accepted. Corporate social responsibilities is considered as information that contains a positive value. It is different from income smoothing management actions that are not responded to by stakeholders. Firm value also has a positive influence on company growth. These results have implications for strengthening the theory of CSR benefits and encouraging companies to present broader information.